Experimental, numerical and exergy analyses of a dual fuel combustion engine fuelled with syngas and biodiesel/diesel blends. (1st April 2020) - Krishnamoorthi, M.; Sreedhara, S.; Prakash Duvvuri, Pavan
Graphical abstract: Highlights: Diesel engine was operated up to 36% syngas energy share in diesel/biodiesel blend. Dual fuel mode reduces PM (77%) and NOx (22%) emissions as compared to diesel case. Soot morphology results show that fine particles were reduced by 67% in syngas case. Simulation depicts that syngas oxidation continues till the late part of the cycle. 90 and 80 kJ/min of exhaust gas and heat transfer availability can be re-utilised. Abstract: This work investigates the effects of addition of syngas and biodiesel on a reactivity controlled compression ignition (RCCI) engine fuelled with diesel. Scanning electron microscopy (SEM) of exhaust particulate matter has been done to obtain particulate matter (PM) morphology. Energy and exergy analyses have been performed to observe energy and availability shares, and to provide directions for the energy recovery systems. Closed cycle combustion simulations have been performed to complement the experimental results and for an improved understanding of in-cylinder dynamics. Chemical and physical properties of three biodiesel samples have been analysed using elemental analysis, Fourier transform infrared spectroscopy and gas chromatography-mass spectrometry. Based on the initial study, used cooking oil based biodiesel blend (B20, 20% biodiesel) has been chosen in experiments. The optimal operating conditions for syngas/diesel and syngas/B20 in RCCI mode for different operating parameters have been investigated. Injection pressure, injection timing and pre-injection mass ratio have been modified to get improved combustion efficiency at mid-load. Syngas/diesel mode with an injection timing of 19° before top dead centre (bTDC) shows slightly higher brake thermal efficiency (BTE) with 22% and 77% lower oxides of nitrogen (NOx) and PM respectively as compared to conventional diesel combustion. In syngas/B20 mode, a maximum BTE of 24% has been observed for the case with a pre-injection at 50° bTDC with 30% mass fraction and 18° bTDC main injection timing. Syngas/diesel shows a reduction in primary soot particle count by about 67% and contains larger aggregates as compared to neat diesel.